PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DENGAN METODE EKSPERIMEN TERHADAP HASIL BELAJAR SISWA - Palilingan, Rolles Nnixon; Tulandi, Djeli Alfi; makaromase, frisilia frisilia (Universitas Negeri Manado, 2020)
ABSTRACT. Research in the background by the lack of interest in student learning. The purpose of this study was conducted to determine the effect of problem based learning models with experimental methods on student learning outcomes. This study uses an experimental method, the population taken from all class X, which consists of science and social classes at Advent Klabat Manado High School, while the sample taken is 1 class as a subject class that is class X science consisting of 24 students. The date analysis technique used is descriptive technique with the assessment of PBL, attitude, psychomotor and is taken and collected from the assessment of the learning process and the results of the pretest and posttest on the material of Sight Sight and Optical Devices. Analysis of the results of this study shows that the application of PBL learning models using experimental methods in the Sense of Sight material and Optical Devices can improve student learning outcomes.Keywords : Learning Outcomes, Sense of Sight, Optical Devices, Problem Based Learning